A study of defects on historic buildings in Malacca / Nor Haya Yahaya - Yahaya, Nor Haya (Faculty of Architecture, Planning and Surveying, 2013)
Nowadays, Malaysia is a country that well-known has a famous on the legacy of historic buildings with outstanding craftsmanship and architecture quality and the past history and event. They form an impressive historic features and heritage of the past work of man. It is important to conserve and preserve historic buildings because they provide a sense of identity and continuity in a fast changing world for future generations. However some of these buildings are at risk from defects and are not being well careand not proper maintenance due to lack of technical knowledge and will hire the high cost for remedial work and maintenances. Historic building is a building that has a significance of a unique architecture which relates to its past history and events of construction. The defects at historic building are commonly occurs at the historic building due to lack of maintenance, lack of awareness to maintain the historic buildings, lack of expertise contractor to carried out the conservation, and climate area. The objectives of the study are to study the types of building defects, to identify and analyze the causes of building defects and lastly to recommend the best method for the remedial work. The research methodology that was carried out by the researcher has to be implementing through at this study. The researcher uses the primary and secondary to gather the information and gain the knowledge. The interviewed and observation that was carried out at the both case study to meet the parties involve especially on the conservation projects. MrLuth and Mrfaiza! who’s the person directly involve during the interviewed session also not forgettable Madam Masyitah Binti Abd Aziz. The finding to this study, the researcher will conclude that, there are found the several types of building defects are commonly occur at the historic buildings. There are some factors govern that causing the building defects at historic buildings. The finding also has been made based on regarding the both case study. Last but not least, the recommendation for the new work especially on the remedial work has been recommended at the end of this study.